2014
DOI: 10.12691/ijdsr-2-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral <i>Candida</i> in β-thalassemia Major and Healthy Population and Their Fluconazole Susceptibility Pattern

Abstract: Objective: Candida constitutes the main yeast flora in the oral cavity. Different species are known with C. albicans being the principal one. In healthy individuals, the balance among the oral microbial flora is maintained. However, this equilibrium might be altered in certain diseases resulting in the predominance of yeast flora over other microorganisms and behave as pathogens. Thalassemias constitute a large group of immunocompromised patients in our country with multiple hematological, immunological and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…20 This study was conducted to assess the antifungal activity of the laboratory extracted Rosemary and Thyme EOs against fluconazole-resistant C. albicans strains isolated from the oral cavity of healthy and diseased individuals from our population. 4 In the present study, it was found that both EOs exhibited significant antifungal activity against C. albicans. In spite of the higher inhibitory activity of Thyme EO using disk diffusion method (Mean ± SD: 42.4 ± 6.5) in comparison to the recorded data regarding Rosemary EO (Mean ± SD: 11.8 ± 2.8), the statistical analysis showed no significant difference between the two means.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…20 This study was conducted to assess the antifungal activity of the laboratory extracted Rosemary and Thyme EOs against fluconazole-resistant C. albicans strains isolated from the oral cavity of healthy and diseased individuals from our population. 4 In the present study, it was found that both EOs exhibited significant antifungal activity against C. albicans. In spite of the higher inhibitory activity of Thyme EO using disk diffusion method (Mean ± SD: 42.4 ± 6.5) in comparison to the recorded data regarding Rosemary EO (Mean ± SD: 11.8 ± 2.8), the statistical analysis showed no significant difference between the two means.…”
Section: Discussionsupporting
confidence: 47%
“…1,2 In the oral cavity, among various Candida species, Candida albicans (C. albicans) comprises the most prevalent one in health and disease. 3,4 It is an opportunistic pathogen as it usually causes infection in individuals with low or suppressed immunity. 5,6 Fluconazole is one of the widely used azole drugs in the clinical settings to treat infections caused by C. albicans or in the prophylaxis to prevent recurrent candidiasis in immunocompromised patients.…”
Section: Introductionmentioning
confidence: 99%
“…The weakened immune system in patients with beta thalassemia major causes immune system abnormalities such as a disturbance in neutrophil and macrophage chemotaxis, phagocytosis and B-lymphocyte cell differentiation, leading to Candida albicans penetration into the tissue. 63 Repeated blood transfusions cause the accumulation of iron in salivary glands and triggers the formation of non-transferrin bound iron (NTBI), which can circulate in plasma and trigger the formation of reactive oxygen species (ROS). ROS are highly active molecules that can cause cell apoptosis and epithelial tissue damage.…”
Section: Candida Albicans Infection In Patients With Beta Thalassemia...mentioning
confidence: 99%